2002
DOI: 10.1097/00002030-200204120-00019
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of women in an African setting: lessons for mother-to-child HIV transmission prevention programmes

Abstract: After discussing advantages and risks, only a third of the 290 HIV-infected women included in an intervention study to reduce mother-to-child transmission of HIV in Mombasa, Kenya, informed their partners of their results. Despite careful counselling, 10% subsequently experienced violence or disruption of their relationship. To increase the uptake of interventions to reduce perinatal HIV transmission safely, we recommend the involvement of partners in HIV testing. In addition, the counselling of women has to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
77
3
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(90 citation statements)
references
References 8 publications
9
77
3
1
Order By: Relevance
“…Similar observations were made in several studies [16,[17][18][19][20][21][22][23][24][25][26][27] that looked at the acceptability of voluntary HIV testing by pregnant women in developing countries. This could be explained by the fact that women who were educated feared HIV testing due to their evaluation of risks or implications of a positive HIV result.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Similar observations were made in several studies [16,[17][18][19][20][21][22][23][24][25][26][27] that looked at the acceptability of voluntary HIV testing by pregnant women in developing countries. This could be explained by the fact that women who were educated feared HIV testing due to their evaluation of risks or implications of a positive HIV result.…”
Section: Discussionsupporting
confidence: 83%
“…Our acceptance rate of VCT was low compared to reports from several countries where interventions to reduce PMTCT were offered to pregnant women [18]. In our study, infant formula was offered later during the post-partum period.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…46 At the same time, studies of PMTCT, although not couple-centred, have also concluded that there was a need to "involve" male partners. 48,49 However, in spite of the available data and repeated recommendations, couple-centred approaches to HIV prevention (whether connected with PMTCT or prevention of sexual transmission) have not been implemented on a large scale or, at least, have not been documented in the literature, where others could learn from them. Apart from the experiences reported in Former Zaïre 37 , Rwanda, 38,57 , Zambia 3,14,43,44 , Kenya 45 , and the multi-site study KenyaTanzania-Trinidad 39,40 , it is hard to find in recent years any mention of a couple-centred approach in the scientific literature or in programmatic documents.…”
Section: Discussionmentioning
confidence: 99%
“…Насилие является одним из жестоких последствий стигмы, с которым стал-киваются, главным образом, женщины [32][33][34]. Женщины и девушки сообщают о росте случаев жестокого обращения со стороны их партнеров в ответ на просьбы пользоваться презервативами, обращение в службы добровольного консультирования и тестирования, отказ от половых отношений в браке или от внебрачного секса или получение положительного результата тестирования на ВИЧ [35][36][37][38].…”
Section: стигма и дискриминация непропорционально сильно затрагивают unclassified